DEKONSTRUKSI FATWA MENGENAI LARANGAN BUNGA BANK (QIYAS VS ISTIHSAN) - Khotibul Umam (Faculty of Law, Parahyangan Catholic University, 2023)
Deconstruction is intended to serve as critique to the method of determining the prohibition status of bank interest, which is analogous to usury, as well as reconstructing the issue with other methods to produce a more implementable fatwa, especially in a pluralistic society. Normative legal research is carried out using a historical approach and a conceptual approach regarding usury and interest, as well as the methods and the rationale for the prohibition of both. Application of analogy (qiyas) can bring